Examining the association between substance use disorder treatment and smoking cessation. (20th March 2015) - Shu, Chang; Cook, Benjamin Lê
Abstract Aims To examine rates of smoking cessation among people with last year substance use disorder (SUD) and how these rates differ among those that have ever received SUD treatment, those who have never received treatment and those who received last year out‐patient and/or in‐patient treatment. Design Cross‐sectional study based on 2009–12 National Survey on Drug Use and Health (NSDUH). Setting and Participants A total of 12 796 adult life‐time smokers with any last year SUD. The sample is representative of the non‐institutionalized US adult population. Measurements We described smoking cessation rates by type of SUD and SUD treatment. We used a logistic regression model identifying the association between smoking cessation and life‐time SUD treatment, adjusting for confounders. We also estimated models identifying the association between smoking cessation and last year out‐patient and in‐patient SUD treatment. Findings Multivariate models identified significantly lower odds of quitting among those with life‐time SUD treatment [odds ratio (OR) = 0.561, P‐value < 0.001] compared with those without SUD treatment. Past year in‐patient and out‐patient SUD treatment was associated with lower odds of quitting in an unadjusted comparison (OR = 0.559, P‐value = 0.043). In multivariate models, associations were suggestive of lower odds of quitting among those in treatment but there were no significant associations between smoking cessation and receiving in‐patient and out‐patient services (OR = 0.753, P‐value = 0.312), in‐patient services only (OR = 0.397, P‐value = 0.192) or out‐patient services only (OR = 0.689, P‐value = 0.214). Conclusions Life‐time smokers with past year substance use disorder who had ever received substance use disorder treatment appear to be less likely to quit smoking than those who have never received treatment. This pattern persists across type of substance use disorder.